Improving stability and curving passing performance for railway vehicles with a variable stiffness MRF rubber joint. (21st February 2017) - Harris, B J; Sun, S S; Li, W H
Abstract: With the growing need for effective intercity transport, the need for more advanced rail vehicle technology has never been greater. The conflicting primary longitudinal suspension requirements of high speed stability and curving performance limit the development of rail vehicle technology. This paper presents a novel magnetorheological fluid based joint with variable stiffness characteristics for the purpose of overcoming this parameter conflict. Firstly, the joint design and working principle is developed. Following this, a prototype is tested by MTS to characterize its variable stiffness properties under a range of conditions. Lastly, the performance of the proposed MRF rubber joint with regard to improving train stability and curving performance is numerically evaluated.